Research on the System of Beneficiary Ratification of Negotiorum Gestio: Reconstruction of Interpretative Theory of Article 984 of the Civil Code - Song, Shuwei (Transactions on Social Science, Education and Humanities Research, 2024)
Article 984 of the Civil Code stipulates the beneficiary ratification system, but the terms are relatively broad, leaving a large room for interpretation. In order to give full play to the system utility of the Civil Code, realize the integration of norms before and after, and reduce the difficulty of judicial application, it is necessary to clarify the contents of the system with the theory of interpretation. There are many modes of beneficiary ratification system in comparative law and different theoretical explanations. The analysis of this Article by the interpretive theory should be based on the balance of interests between the administrator and the beneficiary, and on the basis of clarifying the nature and object of ratification, the specific application of entrustment provisions in the beneficiary ratification system should be explored.